Os silêncios da História: o lugar da mulher no período colonial brasileiro. Uma análise a partir da obra de Mary Del Priore - Carraro, Aline (2023)
The objective of the research is to identify the role that women played in Colonial Brazil. Through the historiographical analysis of the works of historian Mary Del Priore, we will show the social scenarios in which these women were, the expressions and struggles of those who to this day suffer from discrimination, violence and silencing. Knowing about ourselves and our past is essential to understanding the roots of the problems that we still encounter in our daily lives, and, based on this context, I will develop my research work, which is structured into three chapters. In the first, entitled History of women in Colonial Brazil, I will address, in general, the different contexts and environments in which women were inserted at that time. In the second chapter, titled Beauty and sexuality; old age and ugliness, I highlight how, since Colonial Brazil, bodies and clothing gained emphasis and that, often, also censorship. And finally, the third chapter is titled Marriage and Divorce; family and work. The latter will address the manner and functions that women had within their family and marriage, as well as their work environments and representations.